Metodologia procesualizacji zarządzania - między efektywnością a elastycznością - Cieśliński, Wojciech (Methodology of processualization in management – between flexibility and efficency, 2006)
In our paper we described new directions for enterprise management. We presentedmethodology of processualiztion on the background of transformation in Polish enterprises. Processualization of management is a transitional period of changes in functioning of enterprises. Methods used in this area help, firstly, to "unfreeze" the structures, secondly they are the essential ingredient for further development of an enterprise, toward more flexible economic networks.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 432-439